Analysis of the Level of Efficiency, Effectiveness, and Convenience of Using a Pedal Powered Water Pump for Irrigation Activities - Mochammad Hatta; Ida Kusnawati Tjahjani; Nurmawati Nurmawati (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Purpose: Analyze the level of efficiency, effectiveness, and convenience of using a pedal-powered water pump for irrigation activities. Design/methodology/approach: This study uses a qualitative approach by conducting interviews, observations, and documentation on farmers in Carat Village, Pasuruan Regency and conducting descriptive analysis of the data that has been collected. Findings: The results show that the use of a pedal-powered water pump has various benefits, including efficiency, effectiveness, convenience for farmers, and other benefits. Research limitation/implications: This research is limited to land that has the same geographical conditions Practical implications: This research is limited to land that has the same geographical conditions. Originality/value: This research is original Paper type: Research paper